Kombinasi Algoritma Vigenère menggunakan Pembangkit ` Kunci RC4 dan ECB menggunakan Pembangkit Kunci LFSR - Qonita Qurrota A’yun; Auliya Rahman; Syaripuddin (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2026)
This research aims to demonstrate the process of encryption and decryption, as well as the implementation of a program in the form of a Graphical User Interface (GUI), using a combination of the Vigenère Cipher algorithm with an RC4 key generator and the Electronic Code Book (ECB) algorithm with an LFSR key generator. This combination was chosen because the Vigenère Cipher, as a classical algorithm, has a simple substitution structure, while RC4 is able to produce a highly random keystream. Meanwhile, ECB is an efficient modern block encryption method, and LFSR can generate a sequence of random bits based on a polynomial function. Together, these methods form a layered approach to securing messages. The data used in this study consists of plaintext messages in text form chosen by the author. The results show that the encrypted message can be successfully decrypted back into its original form. Therefore, this study proves that combining the Vigenère Cipher algorithm with RC4 and the ECB algorithm with LFSR can be effectively implemented and preserve data authenticity.